Guidance on using real-world evidence from Western Europe in Central and Eastern European health policy decision making - Bertalan Nemeth; Maria Kamusheva; Zornitsa Mitkova; Zsuzsanna Ida Petyko; Antal Zemplenyi; Maria Dimitrova; Konstantin Tachkov; Laszlo Balkanyi; Marcin Czech; Dalia Dawoud; Wim Goettsch; Rok Hren; et al. (Journal of Comparative Effectiveness Research, 2023)
Aim: Real-world data and real-world evidence (RWE) are becoming more important for healthcare decision making and health technology assessment. We aimed to propose solutions to overcome barriers preventing Central and Eastern European (CEE) countries from using RWE generated in Western Europe. Materials & methods: To achieve this, following a scoping review and a webinar, the most important barriers were selected through a survey. A workshop was held with CEE experts to discuss proposed solutions. Results: Based on survey results, we selected the nine most important barriers. Multiple solutions were proposed, for example, the need for a European consensus, and building trust in using RWE. Conclusion: Through collaborationwith regional stakeholders, we proposed a list of solutions to overcome barriers on transferring RWE from Western Europe to CEE countries.